Synthesis and Crystal Structure of Stable Oxyphosphoranes - Mei, Luo; Shao Feng, Lu (Asian Journal of Chemistry, 2016)
Exceptionally stable spiro cyclicoxyphosphoanes were prepared by potassium permanganate oxidation of bis(o-tolyl) phenylphosphine oxide followed by acidification probably involving nucleophilic attack by phosphine oxygen atom on a carboxylic carbonyl group. And its structure was determined by single-crystal X-ray diffraction.